Evaluation of the Effectiveness of Tarantula Cubensis Extract in Cats Diagnosed with Stomatitis - Türkarslan, Faruk; Tanrısever, Murat; Ünsaldı, Emine (My University, 2025)
Stomatitis in cats is an immune response to antigenic stimuli, exacerbated by viral infections. The etiopathogenesis of this disease, which manifests itself with sores in the mouth, has not been fully clarified. Today, in addition to medical treatment, partial or complete molar extractions are also performed. In this study, the results of using tarantula cubensis extract in addition to antibiotic treatment in the treatment of cats diagnosed with stomatitis at the Fırat University Animal Hospital Small Animal Surgery Clinic in Elazığ and the Hekimköy Veterinary Clinic in Adana were investigated. The cats were evaluated in two groups. The cats in the first group (ANT) (n=10) received amoxicillin clavulanic acid treatment, and the cats in the second group (EXT) (n=10) received tarantula cubensis extract injections in addition to the same antibiotic treatment. The response to the treatments was evaluated by 3 different surgeons, one week apart, by macroscopic inspection and scored between 1 and 4. The obtained data were statistically evaluated with the Mann Whitney U test and Wilcoxon tests. In this study, a statistically significant improvement was observed in cats treated with tarantula cubensis extract in addition to antibiotic treatment compared to cats treated with antibiotics alone.
Keywords: Cat; stomatitis; tarantula cubensis extract